Flat start guess homotopy-based power flow method guided by fictitious network compensation control - Silva, Alisson Lima (2022)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2022.